Integration of Life Skills in the Putera Muhammadiyah Kuningan Pencak Silat Training - Oman Hadiana; Herman Subarjah; Amung Ma’mun; Mulyana Mulyana (STKIP Muhammadiyah Kuningan, 2021)
This study aims to develop a model of Pencak silat tapak Suci practice by integrating life skills. The research method used is research and development of the ADDIE model, which consists of 5 stages, namely (1) analysis, (2) design, (3) development, (4) implementation, (5) and evaluation. The sample used was 96 people who were fostered by the pencak silat Tapak Suci branch of STKIP Muhammadiyah Kuningan. The results showed that this training model was valid, practical, and effective. Validity: expert judgment for the material score of 3.98 and expert judgment of the Pencak silat training model resulted in an average score of 3.94, both in the good category. Practical: the average response to the first-class questionnaire was 3.71 (good), the average response to the small group trial questionnaire was 3.84 (good), and the average response to the field trial questionnaire was 3.98 (good). Effectiveness: n-gain test value 0.59 (medium). It can be concluded that the Tapak Suci Pencak silat training model by integrating life skills can be used.